Women's Access to Education and Its Impact on Their Empowerment: A Comprehensive Review - Irshad Ahmad Reshi; Dr T. Sudha; Shabir Ahmad Dar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Abstract: Education has been identified as a crucial factor in women's empowerment, enabling them to participate fully in social, economic, and political spheres. However, women still face significant barriers to accessing education, particularly in developing countries. This paper provides a comprehensive review of the literature on women's access to education and its impact on their empowerment. It examines the various factors that affect women's access to education, including cultural norms, poverty, discrimination, and lack of resources. The paper also highlights the positive impacts of education on women's empowerment, such as improved health outcomes, increased economic opportunities, and greater political participation. Finally, the paper discusses the challenges that remain in ensuring women's access to education and the policies and programs that can help overcome these challenges.